CANDIDE, un modèle économétrique - Waslander, H. (L'Actualité économique)

(untitled) (HEC Montréal, 1975)
AbstractThis introductory text deals in very general terms with CANDIDE and development and application of large models.A brief sketch of the history of CANDIDE precedes a discussion of the extensive disaggregation and medium-term nature of CANDIDE; the two characteristics that set it apart from more traditional models.From his experience with CANDIDE the author then comments on model design and model use. Development of multi-purpose models, in his view, consists of many difficult and often arbitrary choices. He warns against excessive disaggregation, and use of models as black boxes. Finally, he calls for co-ordination of impact studies.